Detection of vancomycin resistance genes in vibrio alginolyticus isolated from seabass, lates calcarifer on east coast, malaysia - Nur Faqihah Mohd ‘Asri (2023)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement on the course DVT 55204- Research Project. Vibrio alginolyticus is a pathogenic gram-negative bacterium that can cause infection in both aquatic animals and humans. The main objectives of this study are (i) to investigate the antibiotic profiles of V. alginolyticus isolated from seabass on the East Coast, Malaysia, and (ii) to determine vancomycin resistance genes towards V. alginolyticus. A total of 19 samples of V. alginolyticus were isolated from seabass fish or known as Lates carcarifer from East Coast, Malaysia. Antibiotic susceptibility test (AST) was conducted using Kirby-Bauer method by using antibiotics like ampicillin (AMP10), cefotaxime (CTX30), cefotetan (CTT30), chloramphenicol (C30), ciprofloxacin (CIP5), erythromycin (E15), cefepime (FEP30), gentamicin (CN10), kanamycin (K30), cephalothin (KF30), nalidixic acid (NA30), rifampicin (RD5), streptomycin (S10), tetracycline (TE30), oxytetracycline (OT30),trimethoprim/sulfamethoxazole (SXT1.25/23.75), vancomycin (VA30). Polymerase Chain Reaction (PCR) was carried out for the detection of vancomycin resistance genes (vanA, vanB, vanC1, vanC2/C3, vanR, vanS, vanH, vanD and, vanE). As a result, 18 resistance patterns were observed in this study. Multiple antibiotic resistance (MAR) index values for Laguna Semerak, Kuala Ibai, and Sungai Besut were 0.29, 0.19, and 0.23, respectively. Laguna Semerak and Sungai Besut show a significant risk of contamination with the high usage of antibiotics. None of the vancomycin resistance genes were found. This study demonstrates a report on multidrug resistance of V. alginolyticus in seabass that could be of concern to the fish farmers. In addition, data from this study can be further used in fish disease management plans. Keywords: Vibrio alginolyticus, Lates calcarifer, vancomycin, antibiotics, resistance gene.